Implementasi Kurikulum Merdeka Belajar (KMB) Pada Mata Pelajaran IPS Terpadu Kelas VIII di MP Panca Setya 2 Sintang - Darsela; Pelipa, Emilia Dewiwati; Thoharudin, Munawar (Jurnal Pendidikan Ekonomi Undiksha, 2024)
Implementing the independent learning curriculum is a form of evaluation of the previous curriculum, namely the 2013 curriculum; the independent curriculum was launched to catch up with education during the COVID-19 pandemic. This research aims to describe the implementation of the independent learning curriculum. The approach used in this research is a qualitative approach with descriptive methods. Data collection techniques include observation, interviews, and documentation. The data sources in this research are primary data, namely teachers, school principals, curriculum assistants, and students. Secondary data are documents and field photos. Data analysis uses the Miles and Huberman interactive model: data collection, data display, data reduction, and conclusion. This research shows that the independent learning curriculum has gone well and smoothly, but teachers need some help implementing it. Disadvantages relate to teachers being required to strive for a more creative learning process and the obstacles they face, namely difficulties in cultivating interest in learning, limited references, uneven access to learning, and time management. To overcome the barriers to the independent learning curriculum, schools and teachers can utilize the independent teaching platform and facilitate learning for citizens by reaching digital access and internet networks.